Analisis Review Penggunaan Sistem Informasi pada PT Pertamina - Wahid Wachyu Adi Winarto (Puslitbang Sinergis Asa Professional, 2021)
The information system is a means of transforming company data which is closely related to the efficiency of the company in its operational activities. Along with technological developments, the application of information technology in the company is an important factor in increasing the value and competitiveness of the company. So far, there are still many companies that have not implemented information systems as expected because there is no standard for supervising the use of information technology within the company. This research tries to find out how the information system implementation at PT Pertamina. The sample selection is because PT Pertamina is a state-owned company with large assets. Data analysis using qualitative analysis using a systematic review approach. The results of this study indicate that PT Pertamina has implemented an information system in the form of a management information system properly in the company as a way to achieve company goals so that efficiency and competitiveness of the company can be achieved.